Tones of Last Official Speech as First Lady by Michelle Obama - Nuri Anggraeni; Lilis Suryani (IKIP Siliwangi, 2019)
This article is an analysis of the last speech script of Michelle Obama as the first lady. This study aims to find out what the tone contained in Michelle Obama's speech, to know the type of tone that is often used by Michelle Obama in her speech, and to investigate the meaning of the tone used. The method used in this research is descriptive qualitative and document as the source of the data. In collecting the data, first, the writers searched for a video of Michelle Obama's speech on the internet, then wrote the speech so that it became a transcript of the speech, after that, the writers did an analysis document by looking for the tone (McCarthy, 2006) used in Michelle Obama's speech. The results of the study showed that Michelle Obama uses all kinds of tone in her speech, namely Rise, Rise-fall, Fall, Fall-rise and Level. The dominant tone used by her is the Rise-fall. Tone Fall shows sadness, fall-rise tone show dissapointment, rise tone show happiness, rise-fall tone express hopeness and the last is level tone to show that speaker certain with her statement. It can be concluded that content of her speech is about motivation.